Latest News on Arabidopsis Brassinosteroid Perception and Signaling - Harter, Klaus; Witthöft, Janika (Frontiers in Plant Science, 2011)
Brassinosteroids (BR) are plant hormones regulating growth and development. In interaction with other hormones, they are involved in environmental cue responses. The “standard” BR response pathway model in Arabidopsis includes the perception of the hormone by the plasma membrane receptor BRASSINOSTEROID INSENSITIVE 1 (BRI1) and its hetero-oligomerisation with the co-receptor BRI1-ASSOCIATED RECEPTOR KINASE 1 (BAK1), followed by the activation of a signaling cascade finally resulting in the expression of BR-responsive genes. Recent findings have shed new light on the molecular mechanism of BR perception, which includes the hormone-induced formation of a platform in BRI1 extracellular domain for interaction with BAK1, and on very early events of signaling at the plasma membrane-cytoplasm interface. In addition, a fast BR response pathway that modifies the membrane potential and the expansion of the cell wall – both crucial processes preceding cell elongation growth – was identified. In this review, these latest findings are summarized and discussed against the background of the “standard” model of BRI1-dependent signaling.